Adjectives in Tourism English on the Web: A Corpus-based Study - Pierini, Patrizia (Círculo de Lingüística Aplicada a la Comunicación, 2013)
The present study aims to explore the ‘phraseology of tourism’, i.e. lexical choices and recurring patterns in discourse with the tools of corpus linguistics. It investigates the use of adjectives in the discourse of accommodation, considering their lexico-semantic, grammatical and pragmatic aspects. The data are extracted from a small and untagged corpus amounting to 196,400 words, compiled at the University of “Roma Tre” by downloading the pages of British hotel Web sites. The methodology consists of two steps. First, a frequency wordlist of the adjectives occurring in the corpus is produced. Then, some of the most frequent adjectives are analysed in concordances to highlight relevant features of accommodation discourse, and to discover collocations. The study tries to integrate a corpus approach into a discourse perspective in the analysis of data, considering situational and functional factors to explain linguistic choices.